Babunyi: Recomposition of Materak Art in Minimalist Music Concept - Al Mubaraq, M. Habib; Panggabean, Della Rosa; Anggraini, Nora; Putra, Vindo Alhamda (Institut Seni Indonesia Padangpanjang, 2025)
The musical composition “Babunyi” (a recomposition of Materak art in the minimalist music concept) is inspired by one of the kompang patterns found in Materak art, specifically the Kurang 1 pattern, which consists of the Induk (parent), Anak 2 (second child), and Anak 3 (third child) patterns. The concept of